Interpreting the Genetic Revolution: A History of Genetic Counseling in the United States, 1930-2000. - Stillwell, Devon (My University, 2013)
This dissertation explores the social history of genetic counseling in the United States between 1930 and 2000. I situate genetic counselors at the interstices of medicine, science, and an increasingly “geneticized” society. My study emphasizes two central themes. First, genetic counselors have played a crucial role in bridging the “old eugenics” and the “new genetics” as mediators of genetic reproductive technologies. Genetic counselors negotiated the rights and responsibilities of genetic citizens in their patient encounters. Discourses of privilege and duty were also extrapolated outward to public debates about the new genetics, demonstrating the highly-politicized contexts in which counselors practice and women make reproductive choices. Second, I interrogate the professionalization process of genetic counseling from a field led by male physician-geneticists in the 1940s and 50s, to a profession dominated by women with Masters degrees by the 1980s and 90s. This transformation is best understood through the framework of a “system of professions,” and counselors’ professional position between “sympathy and science.” These frameworks similarly structured the client-counselor relationship, which also centered on concepts of risk, the promotion of patient autonomy, and the ethics of non-directiveness and client-centeredness. These principles distanced counselors from their field’s eugenic origins and the traditional doctor-patient relationship. I emphasize the voices of genetic counselors based on 25 oral history interviews, and hierarchies of gender, race, and educational status at work in the profession’s history. A study of genetic counseling is an important contribution to the histories of health and medicine, medical sociology, bioethics, disability studies, and gender and women’s studies.
Keywords: genetic counseling; geneticization; system of professions; history of health and medicine; social history; oral history; History of Science, Technology, and Medicine; History of Science, Technology, and Medicine